2003
DOI: 10.1108/09590550310507731
|View full text |Cite
|
Sign up to set email alerts
|

Desperately seeking shelf availability: an examination of the extent, the causes, and the efforts to address retail out‐of‐stocks

Abstract: With all the hype around efficient consumer response (ECR) and the brave new world of technologies, one would believe that retail out‐of‐stocks have gone down over the last ten years. That is wrong. Retailers have been struggling with considerable out‐of‐stocks for decades – with little evidence of improvement. A similar wrong belief is that shoppers are also still unwilling to accept low service levels. In fact, increasingly, consumers switch brands when they do not find the brand they wanted. But retailers m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
263
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(277 citation statements)
references
References 6 publications
7
263
2
5
Order By: Relevance
“…A number of authors have reported on the disadvantages of using backroom inventory: increased labor costs due to the double handling of items, reduced service levels (Corsten and Gruen, 2003), and inventory inaccuracy (Raman et al, 2001). Therefore, under the objective of smoothing the workload during the week, SKUs with larger net shelf space are more suitable candidates to be ordered earlier.…”
Section: Drivers Of Order Advancementmentioning
confidence: 99%
“…A number of authors have reported on the disadvantages of using backroom inventory: increased labor costs due to the double handling of items, reduced service levels (Corsten and Gruen, 2003), and inventory inaccuracy (Raman et al, 2001). Therefore, under the objective of smoothing the workload during the week, SKUs with larger net shelf space are more suitable candidates to be ordered earlier.…”
Section: Drivers Of Order Advancementmentioning
confidence: 99%
“…For example, the operations management literature includes numerous papers on inventory optimization that are applicable to setting planned inventory levels in a retail store. Recently, however, a few pioneering papers (Raman et al 2001a, 2001b, DeHoratius and Raman 2003, Ton and Raman 2004, Corsten and Gruen 2003, Ton and Huckman 2005, Van Donselaar et al 2006) have provided evidence of deficiencies in retail store execution, suggesting that optimized plans might be severely blunted by less than perfect execution. Although these papers have focused mostly on missing inventory, inventory record inaccuracy and inventory replenishment, it is reasonable to suspect that, given the high level of problems with inventories, other aspects of retail execution are imperfect also.…”
Section: Introductionmentioning
confidence: 99%
“…As much as 25% of stock out situations are caused by issues in shelf replenishment [58]. Retailers try to make this process smoother to decrease the discrepancy between the stock data and what is on the shelf (I3E32).…”
Section: Demand Sensing and Segmentationmentioning
confidence: 99%